POST-KEYNESIANISM: EVOLUTION OF KEYNESIAN MACROECONOMICS IN THE 20TH CENTURY - L. N. Artamonova (Vestnik MGIMO-Universiteta)
The article analyzes the development of J.M. Keynes's theory in the second half of the twentieth century due to the works within the new direction of economical science - Post-Keynesianism. It is shown that in free-market economy Keynesian school based of the original Keynesian methodology requires additional studies of state regulation principles and take into account the qualitative changes in the market mechanisms. It is shown that post-Keynesianism has had a significant impact on the subject of research and has taken into account the principles of free enterprise, market pricing, level of price dynamics. All this principles allow realizing the principle of self-regulation of the market mechanism. New approaches to the post-Keynesians role of the state and state regulation combined with the freedom of entrepreneurship are analyzed. Taking into account real changes and economic crises it is necessary to analyze the main directions of development of the Keynesian model of economic regulation with a view to their effective use in shaping economic policy. There are considered the basic directions of development of post-Keynesianism such as Neo-Ricardian theory of value and prices of goods based on direct costs of production in the framework of macroeconomic model by P. Sraffa, information theory of "fundamental" uncertainty of the future by R. Klauder and the theory of financial instability hypothesis by H. Minsky. Their differences within the framework of post-Keynesianism under the subject specialization are considered. It is noted that the development of PostKeynesianism allows to present the latest research in modern Keynesian school within an interdisciplinary approach to economical problems.